Beyond Unity in Diversity: Cosmopolitanizing Identities in a Globalizing World. (February 2013) - Ang, Ien
The greater interconnectivity and interdependence unleashed by globalization are not creating a more harmonious, cosmopolitan humanity. On the contrary, the more global the world becomes, the more insistent particular differences, especially of the nationalist kind, are being articulated around the world, often leading to tension and conflict. This seeming paradox cannot be reconciled through simple mantras of 'unity in diversity'. Rhetorical references to 'a single humanity' to overcome structurally entrenched divisions (as institutionalized in the world system of nation-states) are not sufficient for the attainment of greater pan-human solidarity. In response to this predicament this paper argues for a cosmopolitan perspective, in which a humanistic universalism should not be seen as a static moral ideal, but as a social and political horizon that must be worked towards, but probably never achieved, through a painstaking and continuing process of cosmopolitanization against the grain of powerful modes of particularist closure.